Information System Success Framework based on Interpersonal Conflict Factors - Mohammed Aboaoga; Mohd Juzaiddin Ab Aziz; Ibrahim Mohamed (International Journal of Electrical and Computer Engineering (IJECE), 2018)
Information system success (ISS) has received considerable attention from researchers as it plays an important role in improving the efficiency and productivity of an organization. Several researchers have conducted empirical studies using numerous factors (e.g. organizational, technological, and individual factors) which affect the information system success. However, there are several factors which are related to interpersonal conflict which may affect information system success. The interpersonal conflict is a critical dimension which can greatly influence information system success in a competitive environment such as the financial sector. Therefore, this study introduces a framework to investigate the influence of interpersonal conflict factors on information system success in the Ministry of Finance, Yemen. The study employed a quantitative method which consists of the following steps: survey design, data collection and data analysis. A sample size comprising 130 employees were distributed in the Ministry of Finance, Yemen. Questionnaires were used to collect data from this sample. Data analysis (reliability, validity, correlation and factor analysis) has been carried out using SPSS.  In addition, structural equation modelling (SEM) has been used for evaluation the research model. Based on the experimental results, the findings in this study revealed that the interpersonal factors (interference, disagreement and instability) significantly negatively (at 0.05 level of significance) influence user satisfaction of information system success.